1992
DOI: 10.1128/aac.36.7.1472
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical pharmacology and pharmacokinetics of the anti-hepatitis virus agent 2'-fluoro-5-ethyl-1-beta-D-arabinofuranosyluracil in mice and rats

Abstract: The preclinical pharmacology and pharmacokinetics of 2'-fluoro-5-ethyl-1-13-D-arabinofuranosyluracil (FEAU), a selective inhibitor of herpesvirus and hepatitis virus replication, were investigated in the mouse and rat. Following intravenous (i.v.) Our earlier studies of structure-activity relationships for a series of 2'-fluoro-5-substituted 1-3-D-arabinofuranosyl pyrimidine analogs showed that 2'-fluoro-5-ethyl-1-0-D-arabinofuranosyluracil (FEAU) is a potent agent against herpes simplex virus with high sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Another 5-substituted nucleoside, FEAU, was also developed as an anti-Herpes Simplex agent [33,34] FEAU demonstrated lower cellular toxicity but is still as effective as FIAU to treat cells infected with Herpes Simplex Virus. We [8] and others [35] Mutant HSV1-tk's were initially developed to more effectively utilize acyclovir and ganciclovir (GCV) and to less effectively utilize thymidine to allow for more effective suicide gene therapy [36]. We have attempted to improve the sensitivity of imaging reporter gene expression by using an alternate substrate such as GCV, PCV, and FHBG and the mutant reporter gene HSV1-sr39tk [14].…”
Section: Discussionmentioning
confidence: 99%
“…Another 5-substituted nucleoside, FEAU, was also developed as an anti-Herpes Simplex agent [33,34] FEAU demonstrated lower cellular toxicity but is still as effective as FIAU to treat cells infected with Herpes Simplex Virus. We [8] and others [35] Mutant HSV1-tk's were initially developed to more effectively utilize acyclovir and ganciclovir (GCV) and to less effectively utilize thymidine to allow for more effective suicide gene therapy [36]. We have attempted to improve the sensitivity of imaging reporter gene expression by using an alternate substrate such as GCV, PCV, and FHBG and the mutant reporter gene HSV1-sr39tk [14].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the main nucleoside metabolism pathway directed by the nucleoside transport process might be different in mouse and rat hepatocytes. It has been shown that there are some differences in the clearance of nucleoside analogs in plasma in the mouse and rat (1,8). Although the relationship of these pharmacokinetic differences with our results has not been established, it would be intriguing if the different nucleoside transport pathways are related to species-dependent pharmacokinetics of nucleoside analogs.…”
mentioning
confidence: 58%
“…There has been recent interest in two 18 F-labeled thymidine analogs, [ 18 (17)(18)(19), and hepatitis virus (20) infection. Preliminary results with radiolabeled FEAU and FFEAU have indicated that these compounds have good uptake characteristics in HSV1-tk and HSV1-sr39tk transduced cells, little or no uptake in nontransduced wild-type cells, and have lower abdominal background activity in mice and rats (11,14) compared with that obtained with For these reasons we compared FEAU and FFEAU with a series of other pyrimidine nucleoside derivatives (including FIAU) and with acycloguanosine analogs using a well-established in vitro uptake assay in the RG2TK1 cell line that has maintained stable levels of HSV1-tk expression for over 13 y.…”
mentioning
confidence: 99%